math

posted by .

prove:
2sinx+sin2x = 2sin^3(x)/1-cosx

  • math -

    LS = 2sinx + 2sinxcosx
    = 2sinx(1 + cosx)
    = 2sinx(1 + cosx)(1-cosx)/(1-cosx)
    = 2sinx(1 - cos^2x)/(1-cosx)
    = 2sinx(sin^2x)/(1-cosx)
    = 2sin^3x/(1-cosx)
    = RS

  • math -

    Thank you Reiny!

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Trig

    Verify the identity: tanx(cos2x) = sin2x - tanx Left Side = (sinx/cosx)(2cos^2 x -1) =sinx(2cos^2 x - 1)/cosx Right Side = 2sinx cosx - sinx/cosx =(2sinxcos^2 x - sinx)/cosx =sinx(2cos^2 x -1)/cosx = L.S. Q.E.D.
  2. maths

    hey, i would really appreciate some help solving for x when: sin2x=cosx Use the identity sin 2A = 2sinAcosA so: sin 2x = cos x 2sinxcosx - cosx = 0 cosx(2sinx - 1)=0 cosx = 0 or 2sinx=1, yielding sinx=1/2 from cosx=0 and by looking …
  3. Math - Trig - Double Angles

    Prove: sin2x / 1 - cos2x = cotx My Attempt: LS: = 2sinxcosx / - 1 - (1 - 2sin^2x) = 2sinxcosx / - 1 + 2sin^2x = cosx / sinx - 1 = cosx / sinx - 1/1 = cosx / sinx - sinx / sinx -- Prove: 2sin(x+y)sin(x-y) = cos2y - cos2x My Attempt: …
  4. math

    tanx+secx=2cosx (sinx/cosx)+ (1/cosx)=2cosx (sinx+1)/cosx =2cosx multiplying both sides by cosx sinx + 1 =2cos^2x sinx+1 = 2(1-sin^2x) 2sin^2x + sinx-1=0 (2sinx+1)(sinx-1)=0 x=30 x=270 but if i plug 270 back into the original equation …
  5. math

    Please prove: 2sinx+sin2x = 2sin^3(x)/1-cosx
  6. Trigonometry

    Verify the identity. sin2x/cosx + sinx = 2sinx Solve for all values of x: 6cos2x-7cosx-3=0 If f(x)=cos1/2x-sin2x find the value of f(pi)
  7. Math

    can you prove this equation for me? sin2x X sec2x = 2sinx
  8. Trig (Last URGENT)

    sin2x+cosx=0 , [-180,180) = 2sinxcosx+cosx=0 = cosx(2sinx+1)=0 cosx=0 x1=cos^-1(0) x1=90 x2=360-90 x2=270 270 doesn't fit in [-180,180) what do I do?
  9. maths

    by equating the coefficients of sin x and cos x , or otherwise, find constants A and B satisfying the identity. A(2sinx + cosx) + B(2cosx - sinx) = sinx + 8cosx I got A = 2, B = 3, which the answers said were correct. However, another …
  10. Mathematics-Integration

    Question: Prove that [integrate {x*sin2x*sin[π/2*cos x]} dx] /(2x-π) } from (0-π) = [ integrate {sin x*cos x*sin[π/2*cos x} dx ] from (0-π). My thoughts on the question: We know that integrate f(x) dx from (0-a) = integrate f(a-x) …

More Similar Questions